Ephemeroptera, Plecoptera e Trichoptera em corredeiras de riachos do Parque Estadual Intervales, Estado de São Paulo. - Paciencia, Gabriel de Paula; Yokoyama, Elisa; Bispo, Pitagoras Conceicao; Crisci-Bispo, Vera Lucia; Takebe, Igor Vinicius (My University, 2011)
The fauna of Ephemeroptera, Plecoptera and Trichoptera (EPT) from Intervales State Park has been recorded since the 1990s. As a result of these sampling efforts, we present in this study a list of EPT genera in riffles from streams of Intervales State Park, São Paulo State.
Ephemeroptera, Plecoptera and Trichoptera in Riffles from Streams of Intervales State Park, São Paulo State.